Handbook of Argumentation Theory - van Eemeren, Frans H. author. aut Link
79 illus., 18 illus. in color. eReference.
Keywords: The Handbook Argumentation Theory provides an up to date survey of the various theoretical contributions to the development of argumentation theory for all scholars interested in argumentation, informal logic and rhetoric. It describes the historical roots of modern argumentation theory that are still an important theoretical background to contemporary approaches. Because of the complexity, diversity and rate of developments in argumentation theory, there is a real need for an overview of the state of the art, the main approaches that can be distinguished and the distinctive features of these approaches. The Handbook covers classical and modern backgrounds to the study of argumentation, the New Rhetoric developed by Perelman and Olbrechts-Tyteca, the Toulmin model, formal approaches, informal logic, communication and rhetoric, pragmatic approaches, linguistic approaches and pragma-dialectics. The Handbook is co-authored by Frans H. van Eemeren, Bart Garssen, Erik C.W. Krabbe, A. Francisca Snoeck Henkemans, Bart Verheij and Jean Wagemans, who are a coherent and prominent writing team whose expertise covers the whole field. The authors are assisted by an international Editorial Board consisting of outstanding argumentation scholars whose fields of interest are represented in the volume.